UTILIZATION OF ELECTRONIC FORMS AND RECORDS AND TEACHERS’ PRODUCTIVITY - Lago-Tamaño, Maycee Franz (President University, 2024)
This descriptive – the extent of correlational study determined the extent of utilization of electronic forms and records of the teachers in the District of Lambunao West, Schools Division of Iloilo for the School Year 2016-2017. The one hundred fifty-seven (157) randomly selected teachers who are teaching from Grades I to VI which are all permanently employed excluding the teachers teaching SPED and Kindergarten were the participants of the study. The duly-validated researcher-made instrument was used to gather data. The descriptive statistics used were frequency, percentage, standard deviation, and mean while the inferential statistics used were the Kruskal-Wallis Test, Mann-Whitney Test and Spearman rho. Significance level was set at .05 alpha. All data were computer processed using the Statistical Package for the Social Services (SPSS) software. The finding revealed that generally, as an entire group and regardless of age, civil status and educational attainment the extent of teachers’ utilization of electronic forms and records was high. As an entire group and regardless of age, civil status and educational attainment, the level of teachers’ productivity was very satisfactory. A significant different was noted in the extent of teachers’ utilization of electronic forms and records and their level of productivity. There were also significant differences noted when the teachers’ utilization of electronic forms and records were categorized as to age, civil status and educational attainment.